Effect of Ketorolac on Pharmacokinetics and Pharmacodynamics of 5-Fluorouracil: In Vivo and In Vitro Study - Motahare Atefinezhad; Ahmadreza Moghadamnia; Seyed Parsa Eftekhar; Ali Akbar Moghadamnia; Sohrab Kazemi (Journal of Tropical Medicine)
Background. This study aimed to evaluate the impact of ketorolac on the pharmacokinetics of 5-FU and its effect on the efficacy of 5-fluorouracil (5-FU) on the HT-29 cell line. Methods. Cell culture: the HT-29 cell line was treated with different concentrations of 5-FU, ketorolac, and combination of 5-FU and ketorolac for 24 and 48 hours. The cell viability (%) was calculated by the MTT assay. Animal study: rats were randomly divided into control and pretreatment groups. The control group received physiological saline, whereas the pretreatment group received ketorolac by intraperitoneal (i.p.) injections on a daily basis for 14 days. On the 15th day, both groups received 5-FU (i.p.). Blood samples were collected at different times for HPLC analysis, and 5-FU pharmacokinetic parameters were calculated. Results. At cell culture study, in a certain concentration range, combination therapy showed synergistic effects (<0.05). However, at concentrations above this range, combination therapy showed antagonistic effects on 5-FU efficacy (<0.05). According to the pharmacokinetic analysis, pretreatment with ketorolac resulted in a significant increase in AUC, Cmax, and Tmax of 5-FU (<0.05) and a significant decrease in V/F and Cl/F of 5-FU (<0.05). Conclusions. Combination therapy with ketorolac and 5-FU, depending on time and concentration, has a synergistic effect on reducing the viability of cancer cells. Also, ketorolac is able to alter the pharmacokinetics of 5-FU. Since there is a close relationship between pharmacokinetic parameters of 5-FU and its effectiveness/toxicity, it seems that these changes are towards creating a synergistic effect on 5-FU cytotoxicity. These results suggest the need to optimize the dose of these drugs in order to increase clinical efficacy and reduce the toxicity associated with them.